A contingency theory perspective of environmental management: Empirical evidence from entrepreneurial firms. (October 2021) - Mahmud, Muaz; Soetanto, Danny; Jack, Sarah
This article examines the roles of organizational structure of decision-making and external pressure in determining the practice of environmental management. Using contingency theory, this study argues that having a decentralized structure, entrepreneurial firms are able to adapt to external pressure while implementing environmental management. The data were drawn from 106 small and medium-sized firms in the United Kingdom. The study found that a decentralized structure is positively associated with the practice of environmental management while external pressure from global awareness and social relationships has less impact on firms' environmental management. Interestingly, the impact of decentralized structure on environmental management is strengthened in the context of high level of technological dynamic. Overall, the findings of the study have provided some recommendations to theory and practice of environmental management especially in the context of entrepreneurial firms.